Assessing the uneven global distribution of readership, submissions and publications in applied ecology: Obvious problems without obvious solutions - Nuñez, Martin Andres (2019)
What do Colombia, Indonesia, and Papua New Guinea have in common? Not only are they among the most biodiverse countries in the world, they also face a suite of environmental problems relating to land‐use intensification, climate change, and wildlife management. Yet, at the same time, their capacity to respond to these issues remains weak; a weakness that is exacerbated by a deficit of the scientific research needed to guide policy and application (Barlow et al., 2018).